Protective Effect of Ultraviolet C Irradiation on the Gastric Mucosa of Rats with Chronic Gastritis Induced by Physicochemical Stimulations. (17th March 2021) - Wang, Likang; Chen, Wei; Lin, Xisheng; Zhang, Zhao; Wang, Na; Lv, Youkui; Wang, Xinglin; Gao, Yueming
Abstract : Background . Chronic gastritis (CG) is a common digestive disease with the highest morbidity among multiple digestive diseases, which seriously lowers the life quality of patients. The pathological alternations of gastric mucosa, and its possible mechanisms have been the focus of CG-related researches. Accumulative basic and clinical evidence has confirmed that ultraviolet C (UVC) is effective in relieving superficial acute infective inflammation, skin and mucous membrane injuries, and ulcers, and promoting wound healing. Objective . This study was aimed at investigating the protective effects of UVC on gastric mucosal injury in rats stimulated with physicochemical irritants like ethanol and exploring the mechanisms underlying the protection by UVC against gastric mucosal injury and CG. Methods . Fifty Wistar rats were randomly divided into five groups, including Group A (normal), Group B (model), Group C (omeprazole treatment), Group D (intragastric UVC irradiation for 24 s × 2 yields), and Group E (intragastric UVC irradiation for 48 s × 2 yields). Rats in Groups B–E were made CG model by physicochemical stimulations. All rats were sacrificed one week after the 22-week experiment, and gastric tissues were harvested. Histopathological examinations were performed. The activities of superoxide dismutase and catalase as well as the contents of reduced glutathione and malondialdehyde in gastric mucosal tissues were detected. Serum interleukin-6, interleukin-1beta, tumor necrosis factor-alpha, pepsin, and gastrin were measured. Results . Results showed that physiochemical irritants like ethanol could be used for easily establishing a rat CG model that shared similar pathological features with human CG. Intragastric UVC irradiation could promote the repair of gastric mucosa and improve the atrophy of gastric mucosa by inhibiting the inflammatory factors, increasing the levels of pepsin and gastrin, decreasing the expression of lipid peroxide, and enhancing the activity of superoxide dismutase and catalase and the levels of reduced glutathione. UVC irradiation for 48 s × 2 yields showed the strongest protective effect. Conclusion . UVC irradiation could inhibit the inflammatory factors, activate the antioxidative system, and enhance the secretion of pepsin and gastrin, which promoted the repair of injured gastric mucosa and improved gastric mucosa atrophy.